2016
DOI: 10.3324/haematol.2016.156455
|View full text |Cite
|
Sign up to set email alerts
|

The small FOXP1 isoform predominantly expressed in activated B cell-like diffuse large B-cell lymphoma and full-length FOXP1 exert similar oncogenic and transcriptional activity in human B cells

Abstract: The forkhead transcription factor FOXP1 is generally regarded as an oncogene in activated B cell-like diffuse large B-cell lymphoma. Previous studies have suggested that a small isoform of FOXP1 rather than full-length FOXP1, may possess this oncogenic activity. Corroborating those studies, we herein show that activated B cell-like diffuse large B-cell lymphoma cell lines and primary activated B cell-like diffuse large B-cell lymphoma cells predominantly express a small FOXP1 isoform, and that the 5′-end of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…46 However, the presence of AID and ongoing SHM in the tumors were unanticipated, as we had initially predicted that these would be suppressed in the presence of FOXP1 because we and others have shown that FOXP1 is a transcriptional repressor during the GC reaction that can bind AID and other GC-related genes. 17,18,61 Indeed, we confirmed the reciprocal expression of FOXP1 and AID during the GC transit of B cells in human tonsils and normal murine spleens, and found a direct binding of FOXP1 downstream of AID TSS at 2 discrete intronic peaks, which exhibited strong enhancer chromatin marks and had been previously associated with ubiquitous silencers. 45,62 However, the transcriptional repression of AID by FOXP1 results inefficient in the presence of constitutive NF-kB activation and IRF4 expression, which characterize ABC-DLBCL and are known to be direct strong activators of AID.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…46 However, the presence of AID and ongoing SHM in the tumors were unanticipated, as we had initially predicted that these would be suppressed in the presence of FOXP1 because we and others have shown that FOXP1 is a transcriptional repressor during the GC reaction that can bind AID and other GC-related genes. 17,18,61 Indeed, we confirmed the reciprocal expression of FOXP1 and AID during the GC transit of B cells in human tonsils and normal murine spleens, and found a direct binding of FOXP1 downstream of AID TSS at 2 discrete intronic peaks, which exhibited strong enhancer chromatin marks and had been previously associated with ubiquitous silencers. 45,62 However, the transcriptional repression of AID by FOXP1 results inefficient in the presence of constitutive NF-kB activation and IRF4 expression, which characterize ABC-DLBCL and are known to be direct strong activators of AID.…”
Section: Discussionsupporting
confidence: 75%
“…Upregulation of FOXP1 was expected, as it is broadly recognized as a prognostic indicator and biomarker for human ABC-DLBCL. [59][60][61] In fact, NF-kB activation through IKK2 has been shown to cooperate with FOXP1 to promote lymphoma survival. 46 However, the presence of AID and ongoing SHM in the tumors were unanticipated, as we had initially predicted that these would be suppressed in the presence of FOXP1 because we and others have shown that FOXP1 is a transcriptional repressor during the GC reaction that can bind AID and other GC-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…As Foxp1 depletion did not impair the viability of A20 cells, a targeted CRISPR/Cas9 genome editing strategy was employed to stably silence Foxp1 expression. A strategy was designed to disrupt the expression of both the full-length and short isoforms of the murine Foxp1 protein, as they have been reported to share oncogenic and transcriptional activity in human B cells (22). Transcription from alternate 5 ′ internal promoters generates the smaller FOXP1 proteins in human DLBCL with translation commonly starting in exon 8 (corresponding to exon 6 in the murine Foxp1 ortholog).…”
Section: Stable Foxp1 Depletion In the A20 Cell Line Using Crispr/casmentioning
confidence: 99%
“…FOXP1 ΔN100 is encoded by FOXP1 mRNA lacking exon 6, resulting in translation starting from exon 8 (Table 1 ). FOXP1 ΔN100 is highly expressed in DLBCL patients and predominantly activates B cells, thus contributing to the development of DLBCL [ 98 ]. These insights illustrate the high value of FOXP1 in assessing prognosis and treatment strategies for DLBCL patients.…”
Section: As and Tumor Innate Immune Responsesmentioning
confidence: 99%